Adult Vaccination and Healthy Aging in the UAE: Uptake, Determinants, and Policy Perspectives - Areeba Irfan; Jinnu Jimmy; Zahraa Farhad; Anugraha Lisa Ciju; Reel Louai; Aadith Soorya Arunkumar Maivizhichelvi; Liju Susan Mathew; Sneha Reji; Jayakumary Muttappallymyalil (International Journal of Environmental Research and Public Health, 2026)
Adult vaccination is a critical component of preventive healthcare, reducing morbidity and mortality from vaccine-preventable diseases. Despite established recommendations, adult immunisation coverage remains suboptimal, particularly for vaccines beyond influenza and COVID-19. In the United Arab Emirates (UAE), limited evidence exists regarding adult vaccine uptake and determinants influencing immunisation behaviour within its diverse population. Understanding vaccine-specific coverage and associated sociodemographic, healthcare, and workplace factors is essential to guide targeted strategies that strengthen adult immunisation. A cross-sectional study was conducted among 1330 adults aged ≥ 18 years residing in the UAE. Data were collected using a structured self- or interviewer-administered questionnaire assessing uptake of recommended adult vaccines, including COVID-19, influenza, pneumococcal, herpes zoster, Tdap, and HPV. Sociodemographic characteristics, healthcare access, insurance status, workplace factors, and perceived barriers were also assessed. Descriptive statistics summarised vaccination coverage, and associations between uptake and key determinants were examined using SPSS version 30. Statistical significance was defined as p < 0.05. Overall, 71.0% reported receiving at least one adult vaccine. Uptake was highest for COVID-19 (64.9%) and influenza (57.8%), while pneumococcal, herpes zoster, and Tdap coverage remained low (12–13%). HPV uptake was 22.6% among females and 18.9% among males. Higher uptake was observed among females and adults. Social encouragement, insurance coverage, and healthcare access were associated with vaccination, whereas lack of awareness and logistical barriers hindered uptake. Although overall uptake was moderate, significant gaps persist. Integrating vaccination into routine healthcare services and addressing structural and communication barriers are necessary to improve adult vaccination coverage.